Kedokteran dalam Sejarah Islam - Saepudin, Didin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
Medicine is one of the famous science in Islamic Civilization among the others. There are many scholars in thisdiscipline. I.e. al-Razi, Ibn Sina, al-Biruni, and Ibn Rusyd. The islamic medicine has already influenced Europe civili-zation untill 15th century